Promoting Game-Like Classroom Environment: The Use of Clickers in Teaching, Learning, and Assessment - Yang, Sharon Q.; Congleton, Robert J. (INTI International University, 2011)
Recent studies show that students at all education Levels learn best when classrooms promote participatory activities that re-enforce the material being presented by educators (Mayer fr Johnson, 2010; Rieber & Noah, 2008; Wang, 2008). Activities such as quiz-game 4ike questioning or other game like simulations engage students, make then more attentive during a class, and provide ways a teacher can gain valuable feedback for assessing student learning. Classroom response systems such as clickers are one way to promote teaching, learning, arid assessment in an interactive environment. Clickers are becoming more and more popular in American colleges and universities. Some U.S. higher education institutions even require their students to purchase arid carry their personal clickers between classes. This paper will discuss clicker technology and how it is being used in the classroom for teaching, learning, and assessment in the United States. The paper will, review the research done on classroom response systems, its effectiveness as an instructional technology, how the teaching faculty and students view it, and direction for its future development. The targeted audience Includes classroom faculty who are interested in enhancing their teaching by trying new Instructional technologies. Clickers from Turning Point will be used for examples.